A numerical study of spin torque oscillators based on IMA/PMA bilayer nano-pillars. (12th June 2020) - Yuan, X; Lu, Z; Li, S; Fan, S; Wang, G; Fang, X; Xiong, R
Abstract: In this paper, the magnetization dynamics of bilayer structured nano-pillars containing a fixed layer with perpendicular magnetic anisotropy (PMA) and a free layer with in-plane magnetic anisotropy (IMA) are studied using the micro-magnetic simulation method. Unlike typical sandwich-structured spin-torque nano-pillar oscillators (STNOs), the proposed structure does not contain any nonmagnetic spacer layer. It is found that a stable oscillation with a significant amplitude can be established fast after driving out the vortex core by an in-plane magnetic pulse field. The oscillation frequency and amplitude can be easily manipulated by adjusting the side-length of the nanopillar, the thickness and saturation magnetization of the IMA layer, and an applied magnetic field along z axis. In an array with an adequate inter-pillar distance, the mutual interaction between the nano-pillars will lead the oscillations to be phase-locked, resulting in a considerable enhancement of total amplitude. As it is easy to fabricate these kinds of bi-layer nano-pillars and assemble them in arrays, they may have widespread applications in STNOs.